2016
DOI: 10.1371/journal.pone.0147409
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analyses of Microarray Datasets Identifies ANO1 and FADD as Prognostic Markers of Head and Neck Cancer

Abstract: The head and neck squamous cell carcinoma (HNSCC) transcriptome has been profiled extensively, nevertheless, identifying biomarkers that are clinically relevant and thereby with translational benefit, has been a major challenge. The objective of this study was to use a meta-analysis based approach to catalog candidate biomarkers with high potential for clinical application in HNSCC. Data from publically available microarray series (N = 20) profiled using Agilent (4X44K G4112F) and Affymetrix (HGU133A, U133A_2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…A meta-analysis comprising 15 publically available microarray gene expression data assessing 140 normal and 277 HNSCC samples revealed a list of 181 differentially expressed genes. ANO1 and FADD (both mapped in 11q13) were overexpressed in at least 30% of the TCGA samples (528 HNSCC), and associated with higher risk of recurrence and death [46]. Gains of 11q13.2, including CPT1A, were also associated with worse survival in patients with esophageal carcinoma [47].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis comprising 15 publically available microarray gene expression data assessing 140 normal and 277 HNSCC samples revealed a list of 181 differentially expressed genes. ANO1 and FADD (both mapped in 11q13) were overexpressed in at least 30% of the TCGA samples (528 HNSCC), and associated with higher risk of recurrence and death [46]. Gains of 11q13.2, including CPT1A, were also associated with worse survival in patients with esophageal carcinoma [47].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison across the different sites indicated that 698 genes were common across all the 3 sites (S2 File). The significant gene entities from each site, when cross compared with the previously published database of 181 gene entities (up regulated: 168; down regulated: 13) [21] indicated that 66.3% (n = 119/181) of the genes in the database were identified in tongue cancer, while 109/181 genes (60.22%) were common with laryngopharyngeal subset and 95/181 genes (52.48%) were common with oropharyngeal cancer.…”
Section: Data Mining and Meta-analysismentioning
confidence: 99%
“…The scanned images were analyzed with Feature Extraction Software 10.7 (Agilent) using default parameters (protocol GE1-107_Sep09 and Grid: 072363_D_F_ 20150612). The microarray data across all chips and genes were analyzed using GeneSpring (version 13.0) and normalized by 75 percentile shift (25,26).…”
Section: Real-time Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%